Organelle Genome Variation in the Red Algal Genus Ahnfeltia (Florideophyceae) - Kim, Hocheol; Yang, Ji Hyun; Bustamante, Danilo E.; Calderon, Martha S.; Mansilla, Andres; Maggs, Christine A.; Hansen, Gayle I.; Yoon, Hwan Su (Frontiers in Genetics, 2021)
The agarophyte Ahnfeltia (Ahnfeltiales, Rhodophyta) is a globally widespread genus with 11 accepted species names. Two of the most widespread species in this genus, A. plicata and A. fastigiata, may have diverged genetically due to past geographic changes and subsequent geographic isolation. To investigate this genomic and genetic diversity, we generated new plastid (ptDNAs) and mitochondrial genomes (mtDNAs) of these Ahnfeltia species from four different regions (A. plicata - Chile and UK and A. fastigiata - Korea and Oregon). Two architecture variations were found in the Ahnfeltia genomes: in ptDNA of A. fastigiata Oregon, the hypothetical pseudogene region was translocated, likely due to recombination with palindromic repeats or a gene transfer from a red algal plasmid. In mtDNA of A. fastigiata Korea, the composition of the group II intronic ORFs was distinct from others suggesting different scenarios of gain and loss of group II intronic ORFs. These features resulted in genome size differences between the two species. Overall gene contents of organelle genomes of Ahnfeltia were conserved. Phylogenetic analysis using concatenated genes from ptDNAs and mtDNAs supported the monophyly of the Ahnfeltiophycidae. The most probable individual gene trees showed that the Ahnfeltia populations were genetically diversified. These trees, the cox1 haplotype network, and a dN/dS analysis all supported the theory that these Ahnfeltia populations have diversified genetically in accordance with geographic distribution.